2006
DOI: 10.1159/000094013
|View full text |Cite
|
Sign up to set email alerts
|

Dose Titration to Reduce Dipyridamole-Related Headache

Abstract: Background: Combination of low-dose aspirin and modified-release dipyridamole (ASA+MR-DP) provides a significantly increased benefit in stroke prevention over aspirin alone. However, headaches were reported in more patients receiving dipyridamole-containing agents than in those receiving placebo. We undertook a randomized, double-blind, placebo-controlled trial to evaluate which dosing regimens of ASA+MR-DP have better tolerance. Methods: This trial randomized 146 patients with a history of ischemic cerebrovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 16 publications
1
18
2
Order By: Relevance
“…Upward tapering of the dipyridamole dose may be helpful, 5,6 although this therapy requires further study. Adherence to medication use is an important factor to consider and is affected by costs, side effects, and frequency of dosing.…”
Section: Class III Recommendationmentioning
confidence: 99%
“…Upward tapering of the dipyridamole dose may be helpful, 5,6 although this therapy requires further study. Adherence to medication use is an important factor to consider and is affected by costs, side effects, and frequency of dosing.…”
Section: Class III Recommendationmentioning
confidence: 99%
“…However, only few patients stopped medication due to headache. Regarding the results of other titration studies [8,9,10], we believe the daily use of the combination of 25 mg ASA + 200 mg ER-DP b.i.d. with an initial titration approach of a couple of days to be safe and tolerable for the prevention of ischemic stroke and more effective than aspirin alone [3, 4, 17].…”
Section: Discussionmentioning
confidence: 92%
“…Consequently, the prevalence of headache in stroke patients on DP treatment might be decreased by a dose titration of DP during the initial treatment days, thereby also increasing the compliance of this treatment. Such studies on dose titration to reduce DP-related headache have been performed and showed significantly fewer cases with headache [8, 9] or a less cumulative number of days with headache with an initially reduced dose of DP [10]. Still, in those studies, 1 out of 10 patients stopped medication due to headache [8, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Dipyridamole may cause headache; the incidence of this may be reduced by increasing the dose gradually [323, 324]. …”
Section: Secondary Preventionmentioning
confidence: 99%